AGI grade-guided chaiqin chengqi decoction treatment for predicted moderately severe and severe acute pancreatitis (CAP trial): study protocol of a randomised, double-blind, placebo-controlled, parallel-group, pragmatic clinical trial - Zhiyao Chen; Xiaonan Yang; Jia Guo; Tao Jin; Ziqi Lin; Ping Zhu; Jing Li; Ling Li; Xin Sun; Dan Du; Kun Jiang; Yanqiu He; et al. (figshare, 2022)
Abstract Background Acute pancreatitis (AP) is a common digestive disease with increased incidence globally but without internationally licenced pharmacological therapy. Moderately severe and severe acute pancreatitis (MSAP/SAP) contributes predominately for its morbidities and mortality and has been managed in West China Hospital for decades using the traditional Chinese medicinal formula chaiqin chengqi decoction (CQCQD). The current study tests whether the early administration of CQCQD will result in improved clinical outcomes in predicted MSAP/SAP patients. Methods This is a single-centre, randomised, controlled, double-blind pragmatic clinical trial. AP patients aged 18–75 admitted within 72 h of onset will be assessed at admission for enrolment. We excluded the predicted mild acute pancreatitis (Harmless Acute Pancreatitis Score > 2 at admission) and severe organ failure (Sequential Organ Failure Assessment [SOFA] score of respiratory, cardiovascular, or renal systems > 3) at admission. Eligible patients will be randomly allocated on a 1:1 basis to CQCQD or placebo control administration based on conventional therapy. The administration of CQCQD and placebo is guided by the Acute Gastrointestinal Injury grade-based algorithm. The primary outcome measure will be the duration of respiratory failure (SOFA score of respiratory system ≥ 2) within 28 days after onset. Secondary outcome measures include occurrence of new-onset any organ failure (SOFA score of respiratory, cardiovascular, or renal system ≥ 2) and new-onset persistent organ failure (organ failure lasts > 48 h), dynamic surrogate biochemical markers and clinical severity scores, gut-centred treatment modalities, local complications status, intensive care need and duration, surgical interventions, mortality, and length of hospital stay. Follow-up will be scheduled on 6, 12, and 26 weeks after enrolment to assess AP recurrence, local complications, the requirement for surgical interventions, all-cause mortality, and patient-reported outcomes. Discussion The results of this study will provide high-quality evidence to appraise the efficacy of CQCQD for the early management of AP patients. Trial registration Chictr.org.cn Registry ( ChiCTR2000034325 ). Registered on 2 July, 2020.
Keywords: Medicine; Pharmacology; Biotechnology; Immunology; Cancer; Science Policy; Infectious Diseases; Computational Biology